Recent Geodynamics and Seismicity of the European Arctic - Antonovskaya, Galina (2019)
The recent seismicity and heat flow density are indicators of geodynamic processes. For the European Arctic, the information of recent earthquakes were generalized and compiled on the general seismic catalog for 1998‚Äì2017 based on the new seismic data from stations opened in the region from 2011 to 2016. The general database of the heat flow from different data sources is compiled to obtain its spatial distribution for the European Arctic region. The relationships of heat flow values and seismic activity are discussed for this region, and combined geological and geophysical lithosphere cross sections are made in the latitudinal and meridional directions. The most geodynamic active structures and zones of tectonic stress concentration are distinguished; there are Gakkel Ridge and the Svalbard anticline in the Barents Sea region. Weak seismic events were recorded in the Novaya Zemlya region that reflect manifestations of recent tectonic activity.